Supporting a student with visual impairment in the intensive care unit - Michael Rowe; Tania Steyl; Joliana Phillips; Anthea Rhoda (South African Journal of Physiotherapy, 2019)
Background: The Department of Physiotherapy at the University of the Western Cape began accepting students with visual impairments (VIs) into the undergraduate physiotherapy programme in 1996. However, until recently, none had received a clinical rotation in any high care setting.